Multiplicity dependence of Γ production at forward rapidity in pp collisions at √s=13 TeV - Acharya, S.; Adamova, D.; Adler, A.; Rinella, G. Aglieri; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (ELSEVIER, 2025)
The measurement of Gamma(1S), Gamma(2S), and Gamma(3S) yields as a function of the charged-particle multiplicity density, dN(ch)/d eta, using the ALICE experiment at the LHC, is reported in pp collisions at root s = 13 TeV. The Gamma meson yields are measured at forward rapidity (2.5 < y < 4) in the dimuon decay channel, whereas the charged-particle multiplicity is defined at central rapidity (vertical bar eta vertical bar < 1). Both quantities are divided by their average value in minimum bias events to compute the self-normalized quantities. The increase of the self-normalized Gamma(1S), Gamma(2S), and Gamma(3S) yields is found to be compatible with a linear scaling with the self-normalized dN(ch)/d eta, within the uncertainties. The self-normalized yield ratios of excited-to-ground Gamma states are compatible with unity within uncertainties. Similarly, the measured double ratio of the self-normalized Gamma(1S) to the self-normalized J/psi yields, both measured at forward rapidity, is compatible with unity for self-normalized charged-particle multiplicities beyond one. The measurements are compared with theoretical predictions incorporating initial or final state effects.
Keywords: CHARGED-PARTICLE MULTIPLICITY; NONPROMPT J/PSI PRODUCTION; PROTON-PROTON COLLISIONS; PB-PB COLLISIONS; CHARMONIUM SUPPRESSION; PSI(2S) SUPPRESSION; PROMPT; Physics